Michael quarterly : publication series of the Norwegian Medical Society - Det Norske medicinske Selskab (The Norwegian Medical Society, 2010)
Devoted to research and scholarship in medical history, medical humanities, social medicine and health policy.
Keywords: Medicine : Periodicals; History; Health promotion; Social medicine; Medical historians; Norway; medical history; medical humanities; health policy